The Effect of Financial Skill, Risk Management on Financial Literacy of MSME Actors in West Sulawesi - Naim, Muh. Rezky (PT. Riset Press International, 2025)
This research aims to study how financial and risk management skills impact the financial literacy of MSME actors in West Sulawesi. Small and medium-sized businesses (MSMEs) that contribute to the local economy face many problems, especially concerning effective financial management. This study uses a quantitative approach and collects data through a survey of micro, small, and medium enterprise (MSME) owners in various districts in West Sulawesi. Financial expertise and risk management variables contribute to financial literacy. This was measured through multiple regression data analysis. The results show that financial skills and risk management have a positive and significant effect on the financial literacy of MSME players. Financial skills provide a greater influence than risk management in influencing financial literacy. These findings have significant consequences for developing programs to improve the capabilities of MSME actors that focus on improving financial management skills and understanding of risk mitigation strategies. This research is expected to assist policymakers in making useful interventions to improve the financial knowledge of small and medium-sized businesses (MSMEs) in West Sulawesi.